The epistemology of live blogging. (February 2020) - Matheson, Donald; Wahl-Jorgensen, Karin
This article proposes a typology of the epistemology of live blogging through an analysis of two live news blogs: Radio New Zealand (RNZ) News' live blog of a significant earthquake in Aotearoa New Zealand in November 2016 and BBC News' live blog of the Brexit referendum result in June 2016. We use these cases to draw out five features of the genre that we suggest may characterise other live news blogs. We demonstrate that these blogs tend to (1) produce a fragmentary narrative that (2) reflects particular moments in time, (3) curate an array of textual objects from a range of information sources to produce 'networked balance', (4) gain coherence from an often informal authorial voice or voices and (5) generate claims to knowledge of events which are simultaneously dynamic and fragile. This typology contributes to understanding journalism's position within networked information spaces.